Plastic Waste Management by Fishermen's Groups in Tateli Satu Village - Pelle, Wilmy; Ngangi , Edwin L. A.; Gerung, Grevo; Wantasen, Adnan S.; Rampengan, Royke (Jurnal Ilmiah PLATAX, 2025)
Tateli Satu Village, Minahasa Regency, is a coastal village connected to Manado Bay. Residents living right along the coastline generally work as fishermen and farmers, with a small number working as civil servants or private sector employees. Their highest level of education is generally junior high or high school, with some only graduating from elementary school. Data and field surveys reveal that community sanitation is still inadequate, as evidenced by an unregulated sewerage system. Furthermore, clean water supplies still rely on wells, whose salinity levels are above the standard for domestic consumption. This reflects a lack of understanding among local residents about the importance of water quality and environmental sanitation. Therefore, community partnership programs are crucial for transferring knowledge and technology through soft approaches such as outreach and awareness campaigns. This program is implemented through the provision or introduction of information on water quality standards set by the government (PP No. 22 of 2021). Furthermore, a simple and easy-to-understand introduction of important water quality parameters has been implemented. Another program that has been transferred to the community includes providing information on the requirements for well construction and the importance of complying with government regulations regarding water management, both clean water for consumption and wastewater for sanitation. Specifically, small groups were formed during the activity to demonstrate how to take concrete action when they detect sources of pollution entering the water or water intended for consumption. Keywords: sanitation, water quality, coastal communities, Tateli Satu Village Abstrak Desa Tateli Satu, Kabupaten Minahasa, merupakan salah satu desa pesisir yang masih berhubungan dengan Teluk Manado. Penduduk yang bermukim tepat pada sempadan pantai umumnya bermata pencaharian sebagai nelayan, petani dan hanya sedikit yang berstatus sebagai pegawai negeri sipil dan swasta. Tingkat pendidikan terakhir umumnya SMP dan SMA, sebagian hanya lulus SD. Berdasarkan data dan hasil survey di lapangan terlihat gambaran dimana kondisi sanitasi masyarakat belum begitu layak, dimana tergambar sistem penbuangan air selokan belum teratur. Selain itu ketersediaan air bersih masih mengandalkan sumur yang bersalinitas masih di atas standar kualitas air untuk dikonsumsi rumah tangga. Kondisi ini merefleksikan bahwa sebetulnya masyarakat setempat belum memahami secara benar akan pentingnya kualitas air dan sanitasi lingkungan. Dengan demikian kegiatan program kemitraan masyarakat penting untuk dilakukan guna pentransferan iptek lewat metode pendekatan lunak seperti sosialisasi dan awareness campaign. Program direalisasikan melalui pemberian atau pengenalan infomasi tentang standarisasi kualitas air yang ditetapkan oleh pemerintah (PP. No.22 thn 2021). Di samping itu pengenalan parameter-parameter penting kualitas air secara simpel dan mudah dipahami telah dilakukan. Program lain yang telah ditransfer ke masyarakat ialah pemberian informasi tentang syarat-syarat dalam pembuatan sumur, serta pentingnya mentaati peraturan pemerintah sehubungan dengan pengelolaan air baik air bersih untuk dikonsumsi maupun air-air buangan untuk sanitasi. Secara spesifik telah dibuat kelompok-kelompok kecil (groupwork) saat kegiatan berlangsung untuk mendemonstrasikan bagaimana tindakan nyata saat mereka mendeteksi adanya sumber-sumber pencemar yang masuk ke perairan atau ke dalam air yang akan dikonsumsi. Keywords: sanitasi, kualitas air, masyarakat pesisir, Desa Tateli Satu